2014
DOI: 10.18584/iipj.2014.5.4.1
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Power of Data: A Key Aspect of Sovereignty

Abstract: The lack of good data about U.S. American Indian and Alaska Native populations hinders tribes’ development activities, but it also highlights a space for sovereign action. In coming years, tribes will no doubt continue to advocate for better national data and at the same time increasingly implement their own “data agendas” by gathering high quality, culturally relevant information about their communities. With more meaningful data, tribal policymakers can make informed decisions about which policies and progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Manuscript 3: Although we observe a growing interest and openness towards diversity and inclusion in the sciences, few efforts have addressed the need to reconcile the impacts of centuries of oppression, extractive models of research, and lack of accountability evidenced in the record of colonial-driven research agendas in Indigenous communities (Simpson, 2004;Smith, 2012). Further, Indigenous communities recognize an ongoing need for improving access to data that reflects the needs, knowledges, and priorities of their communities, rather than externally-driven agendas (Moore, Castelden, Tirone, & Martin, 2017;Rainie, Briggs, et al, 2017;Schultz & Rainie, 2014;Whyte, 2018). This conceptual paper and case study summary address this gap through the development of a working model for restoring relational accountability and decolonizing community-based science research with Indigenous communities.…”
Section: Research Gaps Addressed By Dissertation Manuscriptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manuscript 3: Although we observe a growing interest and openness towards diversity and inclusion in the sciences, few efforts have addressed the need to reconcile the impacts of centuries of oppression, extractive models of research, and lack of accountability evidenced in the record of colonial-driven research agendas in Indigenous communities (Simpson, 2004;Smith, 2012). Further, Indigenous communities recognize an ongoing need for improving access to data that reflects the needs, knowledges, and priorities of their communities, rather than externally-driven agendas (Moore, Castelden, Tirone, & Martin, 2017;Rainie, Briggs, et al, 2017;Schultz & Rainie, 2014;Whyte, 2018). This conceptual paper and case study summary address this gap through the development of a working model for restoring relational accountability and decolonizing community-based science research with Indigenous communities.…”
Section: Research Gaps Addressed By Dissertation Manuscriptsmentioning
confidence: 99%
“…In my development of a working model for decolonizing science research, I identified how cross-disciplinary knowledge transfer (as presented through the synthesis in the 3 rd manuscript), along with Indigenous, community-based, participatory action research, and qualitative methodologies (as applied in case studies in the 2 nd and 3 rd manuscripts) can support these efforts. This research also identified specific areas, such as IRB/REB protocols (Brant Castellano, 2004;Cross et al, 2015;Flicker et al, 2007;Riddell et al, 2017) and data stewardship practices (Kukutai & Taylor, 2016;Schultz & Rainie, 2014) where institutions can immediately enact improvements in research standards with Indigenous communities (detailed in the 3 rd manuscript and "actionable methods and resources" within the working model). In terms of academic research, two specific areas in need of continued improvement include revising IRB/REB protocol requirements and grant funding timelines to more effectively support community-driven and designed research protocols that respect the needs of Indigenous communities.…”
Section: Emergent Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting this broader context, some studies present epidemiological data while explicitly referencing major transnational activist goals of promoting indigenous rights to cultural distinctiveness (e.g., King, Smith, & Gracey, 2009 ; Walters, Beltran, Huh, & Evans-Campbell, 2011 ) and sovereignty ( Anderson et al, 2016 ; Schultz & Rainie, 2014 ). Others document how conventional population health statistics reflect limited indigenous input, resulting in erasure and misrepresentation.…”
Section: Introductionmentioning
confidence: 99%
“…Such an initiative should be tribally driven with support and funding from federal, mainstream accreditation, and other entities. An intentional, tribally determined data collection plan for TCUs and tribes would improve TCU and tribal capacity, allow TCUs to better respond to tribal and community needs, and ultimately enhance tribal sovereignty and self‐determination (Cross et al, ; Schultz & Rainie, ).…”
Section: The Data Challenges For Assessing Outcomes For Tribal Collegmentioning
confidence: 99%